Preparation technology and application of nitrogen-doped carbon thin films

By etching and surface modification of the substrate, and using the magnetron sputtering process to control the nitrogen doping process, the problems of metal residue and pyridine N protonation in the existing technology are solved, and the preparation and production of metal-free nitrogen-doped carbon films are achieved. Optimization of ORR catalytic performance, better stability and methanol resistance, and can replace platinum-based catalysts.

CN118522907BActive Publication Date: 2025-01-21CHANGCHUN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410689483.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-30
Publication Date
2025-01-21
Estimated Expiration
2044-05-30

AI Technical Summary

Technical Problem

In the existing preparation methods for nitrogen-doped carbon-based catalysts, transition metals, such as Fe, are often used, which makes it difficult to determine whether the catalytic activity comes from the nitrogen-doped carbon material itself or a metal residue, and when metal is removed in the acidic solution, pyridine N It may be protonated into inactive pyridine N-hydrogen, reducing catalytic activity.

Method used

By etching and surface modification of the substrate, electroactive monomers are introduced, and the nitrogen doping process is controlled through the magnetron sputtering process to effectively control the chemical bonding states of pyridine N, pyrrole N, and graphite N, and optimize the catalytic performance of the carbon film.

Benefits of technology

Achieved the preparation of nitrogen-doped carbon films without metal, optimized the ORR catalytic performance, proved that pyridine N is an effective catalytic active site for ORR, and has better stability and methanol resistance in alkaline solutions, and can replace platinum-based catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118522907B_ABST
    Figure CN118522907B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of thin film preparation, and in particular to a preparation process of a nitrogen-doped carbon thin film and an application thereof, comprising the following steps: S1. substrate cleaning; S2. substrate etching; S3. substrate surface modification; S4. preparation of a nitrogen-doped thin film; S5. high-temperature annealing; the present invention etches the substrate and introduces an electroactive monomer with an electron acceptor effect, which can adjust the electron density on the surface of the substrate, and further through the control of the magnetron sputtering process, under the synergistic effect of the two, realizes effective control of the chemical bond state of pyridine N, pyrrole N and graphite N in the nitrogen doping process, and successfully optimizes the ORR catalytic performance of the prepared carbon thin film catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of film preparation, and in particular to a preparation process of a nitrogen-doped carbon film and its application. Background Art

[0002] The ORR occurring at the cathode of the fuel cell has a very important influence on the actual working efficiency of the fuel cell. Platinum-based catalysts with high catalytic activity and stability in both acid and alkaline solutions are usually used to accelerate the ORR. However, since platinum is a precious metal, it has a high cost, limited production and is very prone to methanol poisoning, so fuel cells are still unable to achieve widespread commercialization. In recent years, nitrogen-doped carbon-based catalysts (such as nitrogen-doped carbon nanotubes, graphene, etc.) have aroused great interest. This is because nitrogen doping can effectively regulate the electrical properties of carbon-based nanomaterials, thereby obtaining higher catalytic performance, and it is expected to replace platinum-based catalysts. However, in the preparation methods of nitrogen-doped carbon-based catalysts reported so far, transition metals (such as Fe) are usually added as catalysts for growing carbon-based nanomaterials, and finally dissolved and removed with an acidic solution, which makes it difficult to judge whether the catalytic activity comes from the nitrogen-doped carbon material itself or some metal residue. In addition, in the process of removing the metal with an acidic solution, the pyridine N, which is speculated to be the catalytic active site, can be protonated into inactive pyridine N-hydrogen, thereby reducing the catalytic activity of the material.

[0003] Therefore, developing a completely metal-free method to prepare nitrogen-doped carbon-based catalysts has become an urgent problem to be solved. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a preparation process for nitrogen-doped carbon film and its application. By etching the substrate and introducing an electroactive monomer with an electron acceptor effect, the electron density on the substrate surface can be adjusted, and further by controlling the magnetron sputtering process, the chemical bond state of pyridine N, pyrrole N and graphite N in the nitrogen doping process can be effectively controlled under the synergistic effect of the two, thereby successfully optimizing the ORR catalytic performance of the prepared carbon film catalyst.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation process of a nitrogen-doped carbon film comprises the following steps:

[0007] S1. Base cleaning: Clean the base material before use to remove stains on its surface;

[0008] S2. Substrate etching: prepare an etching solution and etch the substrate material after step S1 by coating, the etching time is 2-3min, and the ultrapure water ultrasonic cleaning is 20-30min;

[0009] S3. Surface modification of the substrate: preparing a modified electroactive monomer solution, and surface modifying the substrate material treated in step S2 by immersion, removing the substrate material after immersion for 5-6 minutes, and drying;

[0010] S4. Preparation of nitrogen-doped thin film: The treated substrate material is placed in a vacuum chamber. When the background pressure of the vacuum chamber reaches 5×10-4Pa, ionized gas and reactive gas are introduced to deposit a nitrogen-doped carbon thin film on the substrate material by magnetron sputtering.

[0011] S5. High temperature annealing: Place the substrate material on which the nitrogen-doped carbon film is deposited in a high vacuum annealing furnace. When the background pressure of the vacuum chamber reaches 5×10-4Pa, introduce protective gas Ar gas to perform high temperature vacuum annealing on the film.

[0012] Preferably, in S1, the substrate material is one of single crystal silicon or polycrystalline titanium.

[0013] Preferably, in S1, when the substrate material is single crystal silicon, the cleaning method is as follows: ultrasonically cleaning the substrate with acetone, ethanol and ultrapure water for 20-30 minutes in sequence to remove stains on the surface;

[0014] When polycrystalline titanium is used as the substrate material, the specific cleaning method is: boiling it in a hydrochloric acid solution with a volume ratio of hydrogen chloride to water of 1:3 for 30-40 minutes to remove oxides on its surface, and then ultrasonically cleaning it with ultrapure water for 20-30 minutes.

[0015] Preferably, in S2, the etching solution is a mixture of hydrofluoric acid and nitric acid in a molar ratio of 1:3.

[0016] Preferably, in S3, the modified electroactive monomer solution comprises the following components in percentage by mass: 10-20% acrylic acid, 8-10% acrylamide, 15-20% vinyl isocyanate, and the remainder is deionized water.

[0017] Preferably, in S4, the sputtering target used is a high-purity carbon target with a diameter of 6 cm, a thickness of 1 mm and a purity of 99.95%; the ionization gas is Ar gas with a flow rate of 25-30 sccm; the reaction gas is a mixed gas of N2 and CH4 with a flow rate of 20-25 sccm and 5-10 sccm.

[0018] Preferably, in S4, the process parameters of the magnetron sputtering are: RF power of 160-170 W; substrate bias voltage of -12.3 V to 200 V; sputtering time of 40-50 min; and sputtering pressure of 0.5-1 Pa.

[0019] Preferably, in S5, the process parameters of the high temperature vacuum annealing are: a heating rate of 10°C min -1 The annealing temperature is 600-900℃, the holding time is 5-10min, and the temperature drops with the furnace.

[0020] An application of the nitrogen-doped carbon film prepared according to the preparation process in a fuel cell.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. By introducing electroactive monomers and adjusting the substrate bias during deposition and the annealing temperature after deposition, the chemical bond state of N was controlled and the ORR catalytic activity was optimized. It was proved that the catalytic activity of dN-C film for ORR directly depends on the content of pyridinic N in the film, indicating that pyridinic N is an effective catalytic active site for ORR;

[0023] 2. The dN-C film with the highest pyridinic N content not only exhibits the best ORR catalytic activity, but also has better stability and methanol resistance in alkaline solutions than commercial Pt / C catalysts. This pyridinic N-rich metal-free amorphous dN-C film catalyst is expected to replace platinum-based catalysts as cathode catalysts for direct methanol fuel cells and alkaline fuel cells, and has obvious application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a process flow chart of preparing the nitrogen-doped carbon film of the present invention;

[0025] Figure 2 A bar graph showing the content of pyridinic N and pyrrolic N on the surface of the nitrogen-doped carbon film deposited under different substrate bias voltages of the present invention;

[0026] Figure 3 CV graphs of the nitrogen-doped carbon film and Pt / C catalyst for ORR according to Example 1 of the present invention, wherein: (a) Example 1; (b) Comparative Example 2; Test conditions: potential scanning rate of 50 mV s -1 ; The electrolyte was N2-saturated, O2-saturated, and O2-saturated 0.1M KOH solution with 3M CH3OH added;

[0027] Figure 4LSV diagrams of the ORR of nitrogen-doped carbon film, pure carbon film and Pt / C catalyst deposited under different substrate bias voltages of the present invention, wherein the test conditions are: the potential scanning rate is 5mV s -1 ; The electrode rotation speed is 1600 rpm; The electrolyte is 0.1 M KOH solution saturated with O2;

[0028] Figure 5 LSV diagrams of the ORR of nitrogen-doped carbon films and pure carbon films deposited under different substrate bias voltages of the present invention, wherein the test conditions are: the potential scanning rate is 5 mV s -1 ; The electrode rotation speed is 400, 900, 1600, 2500, 3600 rpm; The electrolyte is 0.1 M KOH solution saturated with O2;

[0029] Figure 6 KL diagrams at -0.60 V of nitrogen-doped carbon films, pure carbon films and Pt / C catalysts deposited under different substrate bias voltages of the present invention;

[0030] Figure 7 To test the performance of anion exchange membrane fuel cells with optimized nitrogen-doped carbon film and Pt / C as cathode catalyst;

[0031] Figure 8 The chronoamperometry of the optimized nitrogen-doped carbon film and Pt / C catalyst for ORR, where the test conditions are: electrode potential -0.26 V, electrode rotation speed 1600 rpm; electrolyte is O2-saturated 0.1 M KOH solution;

[0032] Fig. 9 LSV diagrams of the optimized nitrogen-doped carbon film and Pt / C catalyst for ORR before and after 1000 cycles of ADT, where: (a) optimized nitrogen-doped carbon film; (b) Pt / C catalyst; ADT test conditions: potential scanning range: -1 to 0.1 V; potential scanning rate: 100 mV s -1 The electrolyte was 0.1 M KOH solution saturated with O2. The LSV test conditions were as follows: the potential scanning rate was 5 mV s -1 ; The electrode rotation speed is 1600 rpm; The electrolyte is 0.1 M KOH solution saturated with O2;

[0033] Fig.10 The chronoamperometry diagram of the optimized nitrogen-doped carbon film and Pt / C catalyst for ORR, where: test conditions: electrode potential of -0.26 V; electrode rotation speed of 1600 rpm; electrolyte of 0.1 M KOH, saturated with N2 for 0 to 1000 s, saturated with O2 for 1000 to 2000 s, saturated with O2 for 2000 to 3000 s and injected with 3 M CH3OH solution. DETAILED DESCRIPTION

[0034] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] See also Figure 1-10 , the present invention provides a technical solution:

[0036] Example 1

[0037] A preparation process of nitrogen-doped carbon film

[0038] S1. Substrate cleaning: The polycrystalline titanium substrate material was cleaned before use by boiling it in a hydrochloric acid solution of 10 ml of hydrogen chloride and 30 ml of water for 30 min to remove the oxide on its surface, and then ultrasonically cleaned it with ultrapure water for 20 min;

[0039] S2. Substrate etching: 10 ml of hydrofluoric acid and 18.75 ml of nitric acid were mixed to prepare an etching solution, and the substrate material treated in step S1 was etched by coating, the etching time was 2 min, and ultrapure water was ultrasonically cleaned for 20 min to remove the residual etching solution;

[0040] S3. Surface modification of the substrate: 4 g of acrylic acid, 4 g of acrylamide, 8 g of vinyl isocyanate, and 24 ml of deionized water were mixed to form a modified electroactive monomer solution, and the surface of the substrate material treated in step S2 was modified by dipping, and the substrate material was removed after dipping for 5 min and dried;

[0041] S4. Preparation of nitrogen-doped thin films: Place the treated substrate material in a vacuum chamber. When the background pressure of the vacuum chamber reaches 5×10 -4 After Pa, Ar gas, N2 and CH4 mixed gas were introduced to deposit nitrogen-doped carbon film on the substrate material by magnetron sputtering;

[0042] Among them, Ar gas, flow rate is 25sccm; N2 gas, flow rate is 20sccm; CH4 gas, flow rate is 5sccm;

[0043] The RF power was 160W; the substrate bias was -100V; the sputtering time was 40min; the sputtering pressure was 0.5Pa;

[0044] S5. High temperature annealing: The substrate material on which the nitrogen-doped carbon film is deposited is placed in a high vacuum annealing furnace. When the background pressure of the vacuum chamber reaches 5×10 -4After Pa, the protective gas Ar gas is introduced to perform high-temperature vacuum annealing on the film;

[0045] The heating rate is 10℃min -1 The annealing temperature is 700℃, the holding time is 5min, and the temperature drops along with the furnace.

[0046] Example 2

[0047] The only difference between Example 2 and Example 1 is that in Example 2, the substrate bias is a floating bias (-12.3 V), and the remaining steps in Example 1 and Example 2 are exactly the same.

[0048] Example 3

[0049] The only difference between Example 3 and Example 1 is that in Example 3, the substrate bias voltage is -50V, and the remaining steps in Example 1 and Example 3 are exactly the same.

[0050] Example 4

[0051] The only difference between Example 4 and Example 1 is that in Example 4, the substrate bias voltage is -150V, and the remaining steps in Example 1 and Example 4 are exactly the same.

[0052] Example 5

[0053] The only difference between Example 5 and Example 1 is that in Example 5, the substrate bias voltage is -200V, and the remaining steps in Example 1 and Example 5 are exactly the same.

[0054] Comparative Example

[0055] Comparative Example 1: Comparative Example 1 is different from Example 1 in that, in Comparative Example 1, N2 gas is not introduced during deposition, thereby preparing a pure carbon film, and the remaining steps are exactly the same in Comparative Example 1 and Example 1.

[0056] Comparative Example 2: A commercial Pt / C catalyst was purchased as Comparative Example 2, and the Pt / C catalyst was purchased from Hunan Minstrom Zhuang Technology Co., Ltd.

[0057] Performance testing and result analysis:

[0058] The ORR electrocatalytic activity, stability and methanol resistance of the thin film catalyst were characterized in a three-electrode electrochemical electrolysis cell using a PARSTAT 2273 electrochemical workstation. The prepared catalyst was used as the cathode catalyst of an anion exchange membrane fuel cell, and a single cell was made to test the discharge performance of the cell to characterize the catalytic activity of the catalyst in the actual working environment of the fuel cell.

[0059] from Figure 2We can clearly see that when the absolute value of the substrate bias increases to 100V, the content of pyridinic N reaches the maximum, and the content of pyridinic N in the film is about 3 times that of pyrrolic N. Generally speaking, pyridinic N and pyrrolic N are the most common types of N doped in carbon matrices, and since pyridinic N has a lone pair of electrons, it can increase the electron donation ability, which is beneficial to the adsorption of O2 molecules and the breaking of OO bonds, so it is believed to promote a 4-electron transfer ORR and has a higher ORR catalytic activity.

[0060] Table 1 summarizes the total N, pyridinic N, and pyrrolic N contents on the surface of nitrogen-doped carbon films deposited at different substrate bias voltages measured by XPS. As the absolute value of the substrate bias voltage increases from floating voltage to 100 V, the total N content gradually increases from 3.8 at.% to 12.0 at.%, and further increasing the absolute value of the substrate bias voltage leads to a decrease in the total N content. The reason for this change is that increasing the absolute value of the substrate bias voltage can enhance the energy of the bombarding ions during the deposition process, promote the doping of nitrogen atoms into the carbon matrix, and increase the total N content in the carbon film. However, when the absolute value of the substrate bias voltage continues to increase, the excessive bombarding ion energy can easily induce preferential etching of N atoms deposited on the surface of the film, that is, the reverse sputtering phenomenon, resulting in a decrease in the total N content in the film.

[0061] Table 1. Total N, pyridinic N and pyrrolic N contents on the surface of nitrogen-doped carbon films deposited under different substrate bias voltages and ORR electrocatalytic performance parameters of nitrogen-doped carbon films, pure carbon films and Pt / C catalysts

[0062]

[0063] Figure 3 The CV graphs of a typical nitrogen-doped carbon film (Example 1) and a Pt / C catalyst for ORR are shown. As can be seen from the figure, the nitrogen-doped carbon film produces a weak capacitive current in a 0.1M KOH solution saturated with N2, and when the solution is saturated with O2, an obvious ORR peak appears in the CV graph, and an ORR current is generated, indicating that the nitrogen-doped carbon film has catalytic activity for ORR. In addition, when 3M methanol is injected into a 0.1M KOH solution saturated with O2, no change in the ORR current is observed, indicating that the nitrogen-doped carbon film catalyst has good methanol resistance. On the contrary, for the Pt / C catalyst, when 3M methanol is injected into a 0.1M KOH solution saturated with O2, the ORR peak disappears, and the methanol oxidation peak appears, indicating that Pt and methanol react and methanol poisoning occurs.

[0064] Figure 4The LSV graphs of nitrogen-doped carbon film, pure carbon film and Pt / C catalyst deposited under different substrate bias voltages measured in 0.1M KOH solution saturated with O2. When the absolute value of the substrate bias voltage increases from floating voltage to 200V, the turn-on potential and limiting current density of the nitrogen-doped carbon film for ORR first increase and then decrease. When the substrate bias voltage is -100V, the nitrogen-doped carbon film exhibits the highest catalytic activity, and its turn-on potential is the same as that of the Pt / C catalyst, both of which are -0.02V, and the limiting current density is 5.26mA cm -2 The turn-on potential of pure carbon film for ORR is -0.16 V, which is 0.14 V more negative than that of nitrogen-doped carbon film, and the limiting current density is also reduced to 2.56 mA cm -2 , which shows that the catalytic activity of nitrogen-doped carbon film is significantly improved compared with that of pure carbon film.

[0065] In order to further explore the kinetic characteristics of the ORR catalytic activity of nitrogen-doped carbon films, we measured the LSV diagrams of nitrogen-doped carbon films and pure carbon films deposited under different substrate biases at different electrode rotation speeds (400, 900, 1600, 2500, 3600 rpm) ( Figure 5 ). According to the KL formula, we can plot ω at a fixed potential (-0.60V). -1 / 2 and J -1 The relationship curve, namely the KL graph ( Figure 6 ), from the slope and intercept of the curve in the KL diagram, we can calculate the number of electron transfers and the kinetic current density of the catalyst during the ORR process, and the calculated results are summarized in Table 1. From Table 1, we can see that when the absolute value of the substrate bias increases, the number of electron transfers and the kinetic current density first increase and then decrease, indicating that the electrocatalytic activity of the nitrogen-doped carbon film for ORR first increases and then decreases. It is worth noting that the ORR electrocatalytic activity is consistent with the change pattern of the pyridinic N content in the film, that is, the higher the pyridinic N content in the nitrogen-doped carbon film, the stronger the catalytic activity of the film, which shows that pyridinic N in the nitrogen-doped carbon film plays a key role in the catalytic activity and is identified as the catalytic active site of ORR. When the substrate bias is -100 V, the nitrogen-doped carbon film contains the most pyridinic N content (9.4 at.%), and the ORR catalyzed by the film undergoes 4 electron transfer processes and exhibits the highest kinetic current density (29.97 mA cm -2 ), which is 5 times that of pure carbon film (5.95mA cm -2 ) and is comparable to commercial Pt / C catalysts (30.56 mA cm -2 ). In contrast, the ORR catalyzed by pure carbon film undergoes a 2-electron transfer process, which fully proves that the incorporation of N into the carbon matrix can effectively improve the ORR catalytic activity and can transform the ORR from a 2-electron transfer process to a 4-electron transfer process.

[0066] Using the optimized nitrogen-doped carbon film (Example 1) and Pt / C as fuel cell cathode catalysts, the anion exchange membrane fuel cell performance was tested to evaluate the catalytic activity of the catalyst for ORR under actual fuel cell operating conditions. Figure 7 As shown in Figure 2, when nitrogen-doped carbon film and Pt / C are used as catalysts, the open circuit voltage of the fuel cell is 0.99 and 1.00 V, respectively, and the maximum power density is 169 and 191 mW cm, respectively. -2 , indicating that under the actual fuel cell working environment, the nitrogen-doped carbon film catalyst has the same good catalytic activity as the commercial Pt / C catalyst.

[0067] Two methods, chronoamperometric test and accelerated durability test, were used to characterize the stability of nitrogen-doped carbon films. Figure 8 The chronoamperometry of the optimized nitrogen-doped carbon film and Pt / C catalyst in an O2-saturated 0.1M KOH solution at a fixed electrode potential (-0.26V) is shown. It can be seen that the nitrogen-doped carbon film has almost no current loss during the 18000s chronoamperometry test, and the current density remains at 98%. In contrast, for the commercial Pt / C catalyst, the current density is only retained by 76%. Fig. 9 These are the LSV graphs of nitrogen-doped carbon film and Pt / C catalyst before and after 1000 cycles of cyclic voltammetry scanning test. After 1000 cycles of cyclic voltammetry scanning test, the half-peak potential of nitrogen-doped carbon film only shifted negatively by 18mV, while the half-peak potential of Pt / C catalyst shifted negatively by 31mV. These two stability test results fully prove that the stability of nitrogen-doped carbon film in alkaline solution is much higher than that of commercial Pt / C catalyst. The excellent stability of nitrogen-doped carbon film can be attributed to the good bonding between the thin film catalyst and the substrate, which is an important advantage of magnetron sputtering method for preparing thin film catalysts.

[0068] For direct methanol fuel cells, the "methanol permeation" phenomenon is a key issue restricting its application, so we also evaluated the methanol resistance of nitrogen-doped carbon films. Fig.10 The optimized nitrogen-doped carbon film and Pt / C catalyst were tested by chronoamperometry in 0.1M KOH solution at -0.26V electrode potential. N2 was introduced into the solution between 0 and 1000s, O2 was introduced into the solution between 1000 and 2000s, and 3M CH3OH was injected into the solution while continuing to introduce O2 between 2000 and 3000s to evaluate the methanol resistance of the catalyst. Fig.10It can be seen that there is no ORR current between 0 and 1000s. When O2 is introduced into the solution (1000-2000s), both catalysts generate ORR current, and the current density gradually increases. After continuing to inject 3M CH3OH into the solution (2000-3000s), the current density of the nitrogen-doped carbon film has hardly changed, indicating that the nitrogen-doped carbon film has good methanol resistance. On the contrary, for the Pt / C catalyst, the current density is significantly reduced, indicating that methanol poisoning has occurred. Therefore, the excellent methanol resistance of the nitrogen-doped carbon film can be a very obvious advantage for it to replace platinum-based catalysts as a cathode ORR catalyst for direct methanol fuel cells.

[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a nitrogen-doped carbon film, characterized in that: The specific steps include: S1. Base cleaning: Clean the base material before use to remove stains on its surface; S2. Substrate etching: prepare an etching solution and etch the substrate material after step S1 by coating, the etching time is 2-3min, and the ultrapure water ultrasonic cleaning is 20-30min; S3. Surface modification of the substrate: preparing a modified electroactive monomer solution, and surface modifying the substrate material treated in step S2 by immersion, removing the substrate material after immersion for 5-6 minutes, and drying; S4. Preparation of nitrogen-doped carbon film: Place the treated substrate material in a vacuum chamber. When the background pressure of the vacuum chamber reaches 5×10 −4 After Pa, ionized gas and reactive gas are introduced to deposit nitrogen-doped carbon thin film on the substrate material by magnetron sputtering; S5. High temperature annealing: The substrate material on which the nitrogen-doped carbon film is deposited is placed in a high vacuum annealing furnace. When the background pressure of the vacuum chamber reaches 5×10 −4 After Pa, the protective gas Ar gas is introduced to perform high-temperature vacuum annealing on the film; In S3, the modified electroactive monomer solution comprises the following components by mass percentage: 10-20% acrylic acid, 8-10% acrylamide, 15-20% vinyl isocyanate, and the remaining components are deionized water; In S4, the process parameters of the magnetron sputtering are as follows: RF power of 160-170W; substrate bias voltage of -12.3V- -200V; sputtering time of 40-50min; sputtering pressure of 0.5-1 Pa; the sputtering target used is a high-purity carbon target with a diameter of 6 cm and a thickness of 1 mm and a purity of 99.95%; the ionization gas is Ar gas with a flow rate of 25-30 sccm; the reaction gas is a mixed gas of N2 and CH4, with an N2 flow rate of 20-25sccm and a CH4 flow rate of 5-10sccm; In S5, the process parameters of the high temperature vacuum annealing are: the heating rate is 10°C min -1 The annealing temperature is 600-900℃, the holding time is 5-10min, and the temperature drops with the furnace.

2. A process for preparing a nitrogen-doped carbon film according to claim 1, characterized in that: In S1, the substrate material is one of single crystal silicon or polycrystalline titanium.

3. A process for preparing a nitrogen-doped carbon film according to claim 2, characterized in that: In S1, when the substrate material is single crystal silicon, the cleaning method is as follows: ultrasonically cleaning the substrate with acetone, ethanol and ultrapure water for 20-30 minutes to remove stains on the surface; When polycrystalline titanium is used as the substrate material, the specific cleaning method is: boiling it in a hydrochloric acid solution with a volume ratio of hydrogen chloride to water of 1:3 for 30-40 minutes to remove oxides on its surface, and then ultrasonically cleaning it with ultrapure water for 20-30 minutes.

4. The process for preparing a nitrogen-doped carbon film according to claim 1, characterized in that: In S2, the etching solution is a mixture of hydrofluoric acid and nitric acid in a molar ratio of 1:

3.

5. Use of the nitrogen-doped carbon film prepared according to the preparation process according to any one of claims 1 to 4 in a fuel cell.

Citation Information

Patent Citations

  • Preparation method of amorphous C-N thin film electrocatalyst

    CN103386319A

  • Preparation method and application of supercapacitor electrode film

    CN116564721A